In vitro and in vivo radiosensitization with AZD6244 (ARRY-142886), an inhibitor of Mitogen Activated Protein Kinase/Extracellular Signal-regulated Kinase 1/2 kinase - Chung, Eun Joo (2009)
PURPOSE: The Mitogen-activated Protein Kinase (MAPK) pathway is important for cell proliferation, survival and differentiation and is frequently upregulated in cancers. The MAPK pathway is also activated after exposure to ionizing radiation. We investigated the effects of AZD6244 (ARRY-142886), an inhibitor of MEK1/2, on radiation response. EXPERIMENTAL DESIGN: The effects of AZD6244 on the in vitro radiosensitivity of human cancer cell lines (A549, MiaPaCa2 and DU145) was evaluated using clonogenic assays. DNA damage repair was evaluated using γH2AX and mitotic catastrophe was measured using nuclear fragmentation. Cell cycle effects were measured with flow cytometry. Growth delay was used to evaluate the effects of AZD6244 on in vivo tumor radiosensitivity. RESULTS: Exposure of each cell line to AZD6244 prior to irradiation (IR) resulted in an increase in radiosensitivity with dose enhancement factors (DEF) at a surviving fraction of 0.1 ranging from 1.16 to 2.0. No effects of AZD6244 on radiation-induced apoptosis or persistence of γH2AX foci after IR were detected. Cells treated with AZD6244 had an increased mitotic index and decreased Chk1 phosphorylation at 1 and 3 hours after IR. Mitotic catastrophe was increased in cells receiving both AZD6244 and IR compared to the single treatments. In vivo studies revealed that AZD6244 administration to mice bearing A549 tumor xenografts resulted in a greater than additive increase in radiation-induced tumor growth delay (DEF of 3.38). CONCLUSIONS: These results indicate that AZD6244 can enhance tumor cell radiosensitivity in vitro and in vivo and suggest that this effect involves an increase in mitotic catastrophe.